Low-energy electron-induced decomposition of 5-trifluoromethanesulfonyl-uracil: A potential radiosensitizer - Ameixa, J. (2018)
Grant Nos. PD/BD/114447/2016 and PD/BD/114452/2016. researcher position No. IF-FCT IF/00380/2014. Doctoral Training Programme (RaBBiT, PD/00193/2012). S.D. acknowledges support from FWF (P30332). Polish National Science Center (NCN) under the Grant No. UMO-2014/14/A/ST4/00405 (J. R.).